2005
DOI: 10.1007/bf02724085
|View full text |Cite
|
Sign up to set email alerts
|

Primary tubercular osteomyelitis of the sternum

Abstract: Tubercular involvement of the sternum, leading to osteomyelitis, is a rarely described entity even in countries where tuberculosis is endemic. Presentation in pediatric age group is even more uncommon. We describe a 12 year old girl who presented with a mass over the manubruim sterni and fever. CT chest demonstrated a soft tissue mass in the anterior mediastinum, eroding the cortex of the manubrium. Tubercular etiology was suggested by presence of epithelioid granulomas and acid fast bacilli in the Ziehl-Neels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 9 publications
0
42
0
Order By: Relevance
“…Close follow-up is advised in such patients to determine the need for surgical treatment. 14 The role of a history of TB is very important in such cases; however, in this presented case the patient and his parents denied positive history of the disease. The patient did not consider the disease as significant as he was quite young when he suffered from TB.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Close follow-up is advised in such patients to determine the need for surgical treatment. 14 The role of a history of TB is very important in such cases; however, in this presented case the patient and his parents denied positive history of the disease. The patient did not consider the disease as significant as he was quite young when he suffered from TB.…”
Section: Discussionmentioning
confidence: 81%
“…Others believe that aggressive debridement with primary closure is required as an adjunct to chemotherapy to prevent recurrence or the formation of a draining sinus. 13,14 According to some authors, surgery is not indicated in smaller lesions. Close follow-up is advised in such patients to determine the need for surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tubercular involvement of the sternum is rarer even in countries where tuberculosis is highly prevalent [2]. We herein report an unusual case of tuberculous osteomyelitis of sternum with acute presentation as a swelling over anterior chest wall.…”
mentioning
confidence: 85%
“…Patient recovered well at the end of the ATT course without any complication. Tuberculosis of sternum is a rare clinical entity with only few cases reported in literature [6][7][8][9]. Tuli and Sinha reported 14 (1.5%) cases of sternal tuberculosis out of total 980 cases of osteoarticular tuberculosis [10].…”
Section: Case Reportmentioning
confidence: 99%